Grief reactions and impact of patient death on pediatric oncologists. Issue 1 (11th September 2014) - Granek, Leeat; Bartels, Ute; Scheinemann, Katrin; Labrecque, Manon; Barrera, Maru
<x xml:space="preserve">Abstract</x> Background To examine pediatric oncologists' grief reactions to patient death, and the impact patient death has on their personal and professional lives. Procedure The grounded theory method was used. Data was collected between March 2012 and July 2012 at two academic centres in Canada. Twenty‐one out of 34 eligible pediatric oncologists at different stages of their career were recruited and interviewed about their experiences with patient death. Inclusion criteria were: being able to speak English and having had a patient die in their care. The participants formed three groups of oncologists at different stages of career including: fellows, junior oncologists, and senior oncologists who varied in sub‐specialties, gender, and ethnicities. Results Pediatric oncologists reported a range of reactions to patient death including sadness, crying, sleep loss, exhaustion, feeling physically ill, and a sense of personal loss. They also reported self‐questioning, guilt, feelings of failure and helplessness. The impact of these deaths had personal consequences that ranged from irritability at home, feeling disconnected from family members and friends, and becoming more desensitized towards death, to gaining a greater and more appreciative perspective on life. Professional impacts included concern about turnover or burnout at work and improving holistic care as a result of patient deaths. Conclusions Grief over patient death and the emotional labour involved in these losses are a robust part of the pediatric oncology workplace and have major impacts on pediatric oncologist's personal and professional lives. Interventions that focus on how to help pediatric oncologists deal with these reactions are needed. Pediatr Blood Cancer 2015;62:134–142. © 2014 Wiley Periodicals, Inc.